The Influence Of Service Quality And Price On Customer Satisfaction In Sepeda Motor Herman Cv In Nagori Silakkidir - Divayana Marpaung; Anton Luvi Siahaan; Benjamin Albert Simamora (CV Putra Publisher, 2023)
This study aims to see how service quality and price influence customer satisfaction at CV Sepeda Motor Herman in Nagori silakkidir. The type of research used in writing this thesis is in this study the authors use quantitative data, because the data to be obtained is in the form of numbers. The location for the implementation of this research was in Nagori Silakkidir Village, Hutabayuraja District, Simalungun Regency on CV Sepeda Motor Herman. The population in this study were all customers who came to visit CV Herman Motorcycles in Nagori Silakkidir during the period January to March 2023 and the sample used in this study was 35 samples. The data collection techniques that can be used in this study are: interviews, observations, documentation, questionnaires. The data analysis technique used in this study was SPSS version 25. Based on the results of data analysis and hypothesis testing about